Quality Assurance Systems and Student Academic Learning Outcomes among Private Universities: An Ordinal Orbit Regression Analysis - Mapheleba Lekhetho; Christina Maame Pomaah Opoku (Yayasan Nurul Yakin Bunga Tanjung, 2026)
This study examines the relationship between quality assurance (QA) systems and student academic performance and satisfaction in Ghana’s private universities. Guided by total quality management theory, QA is seen as a continuous improvement framework that integrates stakeholder satisfaction, process optimisation, and institutional learning. The study used ordinal probit regression to analyse how students perceive QA in shaping their learning experiences and to evaluate the effects of QA practices on academic performance and satisfaction. Surveys were used to collect data from 281 students in selected private universities. Key QA dimensions included teaching quality improvement, curriculum review, institutional self-assessment, and resource adequacy. Findings show that QA systems are widely institutionalised, but their impact on student outcomes is uneven. Teaching quality improvement is the strongest predictor of academic performance and satisfaction. The findings verify the significance of TQM in higher education institutions. They offer practical guidance for university leaders and regulators to prioritise QA investments that directly enhance teaching, evaluation, assessment, and resource allocation. This alignment can improve student performance, satisfaction, and institutional credibility in competitive higher education environments.